Targeting proteins with halogenated drugs: new strategies to probe halogen-bonding hotspots - Henriques, Bernardo Miguel Vagarinho (2022)
Tese de mestrado, Química (Química) Universidade de Lisboa, Faculdade de Ciências, 2020